Antimicrobial and pharmacological effects of lamiaceae plant leaf extracts in relation to its phenolic and antioxidant activities - Khattak, Muhammad Muzaffar Ali Khan (Submitted to IIUM, 2010)
Leaves of Coleus blumei (two species), Coleus amboinicus (two species), Coleus aromaticus and Pagostemon cablin from Lamiaceae family were collected from different localities, freeze dried and extracted with aqueous methanol. The biological activity in vitro, especially in relation to total phenolic & flavonoid contents, antioxidant and antimicrobial activities were studied. Total phenolic content was determined according to the Folin-Ciocalteu method whilist antioxidant activity was assessed using 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. The antimicrobial activity of the extract was determined by making use of macro dilution and disc diffusion methods on two gram positive bacteria, two gram negative bacteria and on fungus. Furthermore, the toxicity was also assessed for the extracts by performing acute toxicity test. The phenolic content among the six Lamiaceae leaves extract showed significant difference (p<0.05) in result ranging from 55.21 - 95.17 mg GAE/g of dried samples. Pogostemon cablin (PCM) had the highest content of phenolic followed by C. blumei (CBPM). There were significant differences (p<0.05) of IC50 value of six Lamiaceae leaves extract ranging from 10.5 – 34.1 µg/ml. Among the species studied, Coleus amboinicus – Malaysia (CALM) and Pogostemon cablin (PCM) showed higher antioxidant activity compared to the other leaf extracts. All leaf extracts showed activity at least against one strain of bacteria and result showed significant difference (p<0.05) between activities on the five microorganism. On the contrary, all of the leaf extracts were not effective against C. albicans. The minimum inhibitory concentration (MIC) of all leaf extracts ranged from 1.0–2.0 mg/ml in inhibiting the growth of S. aureus, E. Coli, P. aeruginosa and B.subtilis. The acute toxicity test using C. Blumei leaf extract showed that there was no mortality of animals experimented recorded even at the highest dose level of 5000 mg/kg body weight and observed for the 24 hours after administration. This shows that Coleus blumei plant extract have no toxic effect in mice. This study shows that the extracts can be used as antioxidant and antimicrobial agent without having the toxic effect.